We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
397
1
avatar+67 

Use the function rule f(x) = 3x - 4. find each output.

 

1.      F(0)

2.      F (-2)

3      F (3)

 

 

NEED ANSWERs fast!

 Jul 9, 2018
edited by AshleyGordo  Jul 9, 2018
 #1
avatar+7705 
+1

Assuming you mean f(0), f(-2),f(3) instead of F being the antiderivative of f.

f(0) = 3(0) - 4 = -4

f(-2) = 3(-2) - 4 = -10

f(3) = 3(3) - 4 = 5

 

Now assume you mean the antiderivative.

F(0) = 3(0)^2 / 2 - 4(0) = 0

F(-2) = 3(-2)^2 / 2 - 4(-2) = 14

F(3) = 3(3)^2 / 2 - 4(3) = 3/2

 Jul 15, 2018

10 Online Users